Nudging church funding - Smith, Ian K. (Theology, 2026)
Fundraising involves designing mechanisms through which funds are requested and collected. This matters as donation decisions are inevitably influenced by how the funding ask is presented. A subtle change in the design can nudge a donor to choose differently. For churches, practical concerns of financial sustainability need to be balanced against the non-monetary implications of funding mechanisms, including theological considerations. This article explores the links between nudges and funding in various contexts – namely, congregational donations, giving technology and worship; pricing access to cathedral sacred space; church taxes and member participation; and the principle of tithing. Concepts from behavioural science including framing, defaults, inertia, anchoring, priming, social influences and mental accounting are used to address these reflections on church funding.